2021
DOI: 10.12688/aasopenres.13261.1
|View full text |Cite
|
Sign up to set email alerts
|

Low COVID-19 impact in Africa: The multifactorial Nexus

Abstract: Africa has defied predictions of being the worst hit by the novel coronavirus disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, which has devastated Europe, the Americas, and some Asian countries. However, with a current second and third wave of the COVID-19 pandemic across other continents, pertinent​ questions have arisen regarding the lower disease severity and seemingly better outcomes in most African countries. Several factors have been proposed as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
1
7
1
Order By: Relevance
“…It is worthy of note that more than a third of the participants who were SARS-CoV-2 positive were at least 51 years old. Consistent with other studies, we have shown that older individuals are more susceptible to COVID-19 [29,[36][37][38][39]. A reason for such a susceptibility in these older age groups may be attributed to the increased expression in respiratory tissues of the angiotensin-converting enzyme 2 receptor (ACE2R) [7,8].…”
Section: Discussionsupporting
confidence: 88%
“…It is worthy of note that more than a third of the participants who were SARS-CoV-2 positive were at least 51 years old. Consistent with other studies, we have shown that older individuals are more susceptible to COVID-19 [29,[36][37][38][39]. A reason for such a susceptibility in these older age groups may be attributed to the increased expression in respiratory tissues of the angiotensin-converting enzyme 2 receptor (ACE2R) [7,8].…”
Section: Discussionsupporting
confidence: 88%
“…However, it should be noted that other factors could explain the disparities between our results and those of previously cited studies, such as interactions with other polymorphisms or the influence of other risk and protective factors within each population. 26 , 27 Indeed, our results showed a significant correlation between age and the severity of COVID-19 ( p < .001), with severe cases having a median age of 51 years. Additionally, a peak was observed in the age group between 61 and 65 years in the ICU hospitalization group.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, our findings regarding the lack of association of these polymorphisms in our cohort could explain the low impact of the COVID-19 pandemic and the lower severity of SARS-CoV-2 infected patients in Morocco compared with Europe, America and Asia. 26 …”
Section: Discussionmentioning
confidence: 99%
“…It comprises 54 independent nations, many of which are referred to as fragile states [2,3]. Original predictions indicated that Africa would be disproportionately affected by COVID-19 [4], also in view of the difficulty of implementing effective measures of social distancing [5]. The first case of COVID-19 was reported in Egypt on 14 February 2020 [6].…”
Section: Covid-19 In Africamentioning
confidence: 99%
“…However, despite the overall lower number of individuals that were reported to have developed severe symptoms [4], COVID-19 in Africa is still a threat. The precarious situation, characterized by a variety of infectious diseases, malnutrition, and limited access to healthcare, has worsened since the pandemic occurred [27,28].…”
Section: Covid-19 In Africamentioning
confidence: 99%